2021
DOI: 10.1371/journal.pone.0251810
|View full text |Cite
|
Sign up to set email alerts
|

Intense intestinal carriage and subsequent acquisition of multidrug-resistant enterobacteria in neonatal intensive care unit in Morocco

Abstract: This study was conducted in order to know the colonization rate of MDR enterobacteria in neonates during their hospitalization in neonatal intensive care unit (NICU). Furthermore, we investigated risk factors for potential colonization and molecular epidemiology of isolated resistant bacteria. This prospective study was carried out in the neonatology and intensive care unit department of the University Hospital of Fez (Morocco) from February 2013 to July 2015. All consecutive admitted newborns were screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The distribution of MDRs by origin of samples showed relatively high rates in blood cultures (37.7%) and rectal carriage (35.2%) in neonates. These results are in conformity with that of Zou et al, 2021 in China and Arhoune et al, 2021in Morocco [12,13]. Several works have, in addition, shown that the main correlative risk factors for the emergence of MDRs in newborns have been low birth weight, gestational age, long hospital stay associated with prematurity and cumulative antibiotic exposure, among others [14][15][16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of MDRs by origin of samples showed relatively high rates in blood cultures (37.7%) and rectal carriage (35.2%) in neonates. These results are in conformity with that of Zou et al, 2021 in China and Arhoune et al, 2021in Morocco [12,13]. Several works have, in addition, shown that the main correlative risk factors for the emergence of MDRs in newborns have been low birth weight, gestational age, long hospital stay associated with prematurity and cumulative antibiotic exposure, among others [14][15][16].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, more than 45% of E-ESBL were isolated from neonatal rectal carriage. Studies conducted in Morocco have shown prevalence of 22.4% at the time of admission of newborns to the neonatal unit and 92.4% during their stay in the unit [13]. Other authors have reported a rate of 77% of rectal carriage E-ESBL in this age group [27].…”
Section: Discussionmentioning
confidence: 88%
“…In general, prevalence of MDR colonization in hospitalized neonates varies widely, with rates in Western countries varying from 1% in USA [23], to up to 25% in Germany [9] and 30% in Italy [21]. Much higher frequencies were recorded in less developed countries such as Morocco (60%) [24], Ethiopia (74%) [25] and Madagascar (>70%) [26]. Unlike other studies, we focused on early MDR colonization in the first week of life among hospitalized preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia (2017-2018), gut carriage with ESBL-producing Kp (ESBL-Kp) or ESBL-producing Ec (ESBL-Ec) was recorded in 59% of the hospitalized pre-term neonates; previous hospitalization, delivery by cesarean section, and mechanical ventilation were associated with colonization [68]. In a study from Morocco (2013Morocco ( -2015, up to 59.4% and 12.5% of the neonatal ICU (NICU)-patients were colonized with ESBL-Ent and CPE, respectively [69]. CPE carriage was also observed in 8.6% of inpatients in a pediatric hospital in China (2019), with those colonized having a history of invasive procedures and antibiotic exposures [70].…”
Section: Hospital Settingmentioning
confidence: 99%